Implementation of 2-bit multiplier based on electro-optic effect in Mach–Zehnder interferometers - Kumar, Santosh; Bisht, Ashish; Singh, Gurdeep; Amphawan, Angela (Springer US, 2015)
This paper demonstrates the structure and working principle of an optical 2-bit multiplier using lithium niobate (LiNbO3) based Mach–Zehnder interferometer (MZI). The powerful ability of MZI structures to switch the optical signal from one output port to the other output port has been used in the implementation of the proposed 2-bit multiplier. The paper constitutes the mathematical description of the 2-bit multiplier and thereafter compilation using MATLAB. The study is carried out by simulating the proposed device with Beam propagation method (BPM).